2020
DOI: 10.2478/sjph-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric characteristics of the Croatian and the Serbian versions of the oral health impact profile for edentulous subjects, with a pilot study on the dimensionality

Abstract: IntroductionThe aim was to adapt the Croatian and the Serbian versions of the Oral Health Impact Profile for the edentulous population (OHIP-EDENT-CRO and OHIP-EDENT-SRB).MethodsThe translation and cross-cultural adaptation were carried out in accordance with accepted international standards. A total of 95 and 177 removable denture wearers were recruited in Croatia and Serbia respectively. The reliability was evaluated by calculating Cronbach’s alpha coefficient and by test-retest (30 participants in each coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Therefore, we designed a clinical prospective cross-over study based on dental patient self-reported measures, i.e., OHRQoL and OES. The OHIP-EDENT questionnaire has already been psychometrically validated in many countries and languages and was a logical choice for assessing OHRQoL for edentulous patients ( 28 , 30 - 33 ). After the first day of new denture wearing, the OHIP EDENT scores gradually increased through the 3 rd and the 8 th day and then gradually decreased (the 15 th day) and reached the lowest values after 30 days in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we designed a clinical prospective cross-over study based on dental patient self-reported measures, i.e., OHRQoL and OES. The OHIP-EDENT questionnaire has already been psychometrically validated in many countries and languages and was a logical choice for assessing OHRQoL for edentulous patients ( 28 , 30 - 33 ). After the first day of new denture wearing, the OHIP EDENT scores gradually increased through the 3 rd and the 8 th day and then gradually decreased (the 15 th day) and reached the lowest values after 30 days in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…One day after the new CD or MDI-OD delivery, the patients had to fill in data about gender, age, and their previous dental status [fixed partial denture or natural teeth (FPD); removable partial denture (RPD)]. They also had to fill in the validated questionnaires, i.e., the OHIP-EDENT questionnaire consisting of 19 questions ( 28 ) and the orofacial esthetic scale (OES), consisting of eight questions ( 29 ). The OHIP-EDENT comprised 19 questions with answers from 0 (without problems) to 4 (maximum problems).…”
Section: Methodsmentioning
confidence: 99%
“…Orofacial esthetics is one of the most important factors in oral health related quality of life (OHRQoL) of dental patients ( 17 - 21 ). The appearance of teeth, gums, and jaws is restored and changed by a large number of restorative, prosthodontic, periodontal, orthodontic and other oral interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The OHIP-EDENT-19 is proved to be a precise, reliable and useful valid tool for assessing the quality of life related to oral health. 41 The frequency of oral problems is evaluated by OHIP-EDENT-19, which also provides a profile of how these problems might influence a subject's life.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The OHIP‐EDENT‐19 questionnaire is a 19 question, easy‐to‐use and trustworthy tool for assessing oral health‐related quality of life. The OHIP‐EDENT‐19 is proved to be a precise, reliable and useful valid tool for assessing the quality of life related to oral health 41 . The frequency of oral problems is evaluated by OHIP‐EDENT‐19, which also provides a profile of how these problems might influence a subject's life.…”
Section: Introductionmentioning
confidence: 99%